Critical reflections on an interprofessional collaboration to develop domestic violence curriculum in an undergraduate dentistry program. Issue 2 (4th March 2023) - Carrington, Ann; Croker, Felicity; Lee-Ross, Amanda; Keogh, Sandra; Dewar, Simone
ABSTRACT: There is growing recognition of the critical need to incorporate Domestic Violence (DV) curriculum into dentistry degrees. Interprofessional collaboration between Social Work, DV sector and Dentistry developed and delivered the Dentistry and Domestic Violence – Recognise, Respond and Refer (DDV-RRR) program within an undergraduate dentistry degree in Australia. This article presents our critical reflections on the collaboration, development and delivery of this program. Selected questions from Fook's critical reflection model were utilised to guide the reflection process. Key learnings from this process include acknowledging inherent challenges, power and barriers in collaborative projects; importance of interprofessional collaboration for best practice; and the importance of interpersonal/professional relationships for forming and maintaining interprofessional collaborations. We share the learnings from our critical reflections as an example of how interprofessional collaboration enhances the development and delivery of DV curriculum in one undergraduate dentistry course.